The receptor for interleukin 3 is selectively induced in human endothelial cells by tumor necrosis factor alpha and potentiates interleukin 8 secretion and neutrophil transmigration. - Korpelainen, E I (1993)
Interleukin (IL)-3 stimulates hemopoiesis in vitro. However, IL-3 is not normally found in bone marrow, raising doubts as to the in vivo role of IL-3. We have found that human umbilical vein endothelial cells (HUVEC) express functional high-affinity receptors for IL-3 after stimulation with tumor necrosis factor alpha (TNF-alpha), IL-1 beta, or lipopolysaccharide, and that this receptor is involved in inflammatory phenomena. TNF-alpha caused time- and dose-dependent up-regulation of mRNA for the IL-3 receptor alpha and beta chains, with maximal effects occurring 16-36 h after stimulation with TNF-alpha at 100 units/ml. Induction of mRNA correlated with protein expression on the cell surface as judged by monoclonal antibody staining and by the ability of HUVEC to specifically bind 125I-labeled IL-3. Scatchard analysis under optimal conditions of TNF-alpha stimulation revealed approximately 1500 IL-3 receptors per cell, which were of a high-affinity class (Kd = 500 pM) only. In contrast to a previous report, receptors for granulocyte-macrophage colony-stimulating factor could not be detected. IL-3 binding to TNF-alpha-activated HUVEC enhanced IL-8 production, E-selection expression, and neutrophil transmigration. The selective induction of a functional IL-3 receptor on endothelial cells suggests that, beyond hemopoiesis, IL-3 may have an important role in chronic inflammation and in allergic diseases.